Metal matrix composites: revolutionary materials for shaping the future - Km. Pooja; Nazia Tarannum; Pallavi Chaudhary (Discover Materials)
Abstract Research on composite materials has increasingly replaced traditional materials and alloys in an effort to create effective and lightweight solutions for a range of applications. Metal Matrix Composites (MMCs) offer several advantages over other composites, including reduced density, improved strength-to-weight ratio, enhanced resistance to wear and abrasion, and lower thermal expansion coefficient. This review focuses on MMCs based on aluminum, copper, magnesium, titanium, and zinc including their alloys. It examines their physical and mechanical properties, fabrication techniques (e.g., liquid-phase, solid-phase, and In-situ processing), and recent advancements. MMCs have shown remarkable improvements in their properties. This makes them suitable for critical applications in aerospace, automotive, and electronics. Key findings highlight their ability to overcome the weaknesses of traditional materials by enhancing various mechanical properties. They achieve improvements in tensile strength, density, thermal expansion coefficient, elasticity modulus, toughness and fracture resistance, fatigue resistance, creep resistance, and electrical conductivity through reinforcement techniques. The article also highlights the importance of selecting suitable fabrication methods to achieve desired characteristics while minimizing costs and defects. This review serves as a comprehensive guide for researchers and industry professionals. It highlights current trends, challenges, and the significant potential of MMCs as materials for the future. Graphical Abstract